What is the optimal recall period for verbal autopsies? Validation study based on repeat interviews in three populations. Issue 1 (December 2016) - Serina, Peter; Riley, Ian; Hernandez, Bernardo; Flaxman, Abraham; Praveen, Devarsetty; Tallo, Veronica; Joshi, Rohina; Sanvictores, Diozele; Stewart, Andrea; Mooney, Meghan; Murray, Christopher; Lopez, Alan
Abstract Background One key contextual feature in Verbal Autopsy (VA) is the time between death and survey administration, or recall period. This study quantified the effect of recall period on VA performance by using a paired dataset in which two VAs were administered for a single decedent. Methods This study used information from the Population Health Metrics Research Consortium (PHMRC) Study, which collected VAs for "gold standard" cases where cause of death (COD) was supported by clinical criteria. This study repeated VA interviews within 3–52 months of death in PHMRC study sites in Andhra Pradesh, India, and Bohol and Manila, Philippines. The final dataset included 2113 deaths interviewed twice and with recall periods ranging from 0 to 52 months. COD was assigned by the Tariff method and its accuracy determined by comparison with the gold standard COD. Results The probability of a correct diagnosis of COD decreased by 0.55 % per month in the period after death. Site of data collection and survey module also affected the probability of Tariff Method correctly assigning a COD. The probability of a correct diagnosis in VAs collected 3–11 months after death will, on average, be 95.9 % of that in VAs collected within 3 months of death. Conclusions These findings suggest that collecting VAs within 3 months of death may improve the quality of the information collected, taking the need for a period of mourning into account. This study substantiates the WHO recommendation that it is reasonable to collect VAs up to 1 year after death providing it is accepted that probability of a correct diagnosis is likely to decline month by month during this period.